(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In the present study the egg batches and scales of 5 different Thaumetopoea species, collected from 12 localities, were compared. The possibilities of differenciating these species and the relationships within them are discussed with the help of the egg batches and the shape of the scales. The egg batches of T. processionea are quite different from the others. More aver the scales are smaller and pointed. In T. pinivora and T. bonjeani the scales were more or less of the same size, but the egg batches differed in colour and structure. The scales in T. wilkinsoni and T. pityocampa were found to be larger and wider than in the other species. T. wilkinsoni possessed somewhat round scales: in an average, they have more or less the same width as in T. pityocampa but are shorter than in their sister species. The scales at the base, in generai, and at the top, in most cases, of the egg batches were smaller than those from the middle. It is, therefore, to suggest to use the scales from the middle for the taxonomic studies due to their uniform shape.